2009
DOI: 10.1128/aem.00380-09
|View full text |Cite
|
Sign up to set email alerts
|

Diet-Induced Metabolic Improvements in a Hamster Model of Hypercholesterolemia Are Strongly Linked to Alterations of the Gut Microbiota

Abstract: The mammalian gastrointestinal microbiota exerts a strong influence on host lipid and cholesterol metabolism. In this study, we have characterized the interplay among diet, gut microbial ecology, and cholesterol metabolism in a hamster model of hypercholesterolemia. Previous work in this model had shown that grain sorghum lipid extract (GSL) included in the diet significantly improved the high-density lipoprotein ( ). Molecular analysis of the hamsters' fecal bacterial populations by pyrosequencing of 16S rRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
243
1
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 306 publications
(261 citation statements)
references
References 48 publications
12
243
1
3
Order By: Relevance
“…An alternative mechanism for the cholesterol lowering effect of sorghum lipid extract was reported by Martinez et al (81) from research done with hamsters. They reported that sorghum lipid extract acts as a "prebiotic" to improve the host cholesterol metabolism through effects on gut microbiota.…”
Section: Lipidsmentioning
confidence: 97%
See 1 more Smart Citation
“…An alternative mechanism for the cholesterol lowering effect of sorghum lipid extract was reported by Martinez et al (81) from research done with hamsters. They reported that sorghum lipid extract acts as a "prebiotic" to improve the host cholesterol metabolism through effects on gut microbiota.…”
Section: Lipidsmentioning
confidence: 97%
“…Bifidobacteria significantly increased in the hamsters fed grain sorghum lipid extract and was positively associated with HDL plasma cholesterol levels. (81) In humans, this shift in bifidobacteria is associated with improved overall health, including reduced gut infections and suppression of colon cancer initiation. (82)(83)(84) Finally, sorghum lipids may also possess antiproliferation properties.…”
Section: Lipidsmentioning
confidence: 99%
“…In addition to enhancing the abundance of strain IVS-1, the synbiotic used here also redressed the high-fatdiet-induced reduction in the level of bifidobacteria detected in rats that is often reported in the literature (41)(42)(43). Therefore, although no metabolic benefits were seen in the rat model used in our study, the synbiotic may be beneficial in other scenarios, as bifidobacteria are considered health-promoting organisms (6,26,(66)(67)(68).…”
Section: Discussionmentioning
confidence: 62%
“…A total of 28 individual colonies (2 to 3 per subject) were propagated. To classify isolates, DNA was extracted by using the phenol-chloroform extraction method (26), and the 16S rRNA gene was amplified by using the 8F and 1391R universal primers. The amplification product was purified (QIAquick PCR purification kit; Qiagen Inc., MD) and sequenced by a commercial provider (Eurofins MWG Operon, Huntsville, AL).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation